2004
DOI: 10.1038/sj.ejcn.1602067
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status, well-being and functional ability in frail elderly service flat residents

Abstract: Objective: To investigate nutritional status and its relationship to cognition, well-being, functional ability and energy intake in frail elderly service flat residents. Design: Cross-sectional and prospective study. Setting: Two municipal service flat complexes. Subjects: A total of 80 residents (median age 85.5 (79-90) y) with regular home care assistance participated. A subgroup of 35 residents took part in a re-examination 1 y later. Methods: Mini Nutritional Assessment (MNA), Short Portable Mental Status … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
61
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(69 citation statements)
references
References 38 publications
5
61
1
2
Order By: Relevance
“…Such a relationship between ADL and PEM in nursing home elderlies well agrees with the results of previous studies that ADL had the highest power to affect PEM, followed by chewing capacity and cognitive function (8,9). However, these studies were either cross-sectional (8) or longitudinal but only for 1 year (9). Thus, the present data of 3-years duration with prospective surveillance, will give the most reliable confirmation regarding the relation between ADL and subsequent PEM in aged subjects at nursing home.…”
Section: Discussionsupporting
confidence: 80%
“…Such a relationship between ADL and PEM in nursing home elderlies well agrees with the results of previous studies that ADL had the highest power to affect PEM, followed by chewing capacity and cognitive function (8,9). However, these studies were either cross-sectional (8) or longitudinal but only for 1 year (9). Thus, the present data of 3-years duration with prospective surveillance, will give the most reliable confirmation regarding the relation between ADL and subsequent PEM in aged subjects at nursing home.…”
Section: Discussionsupporting
confidence: 80%
“…Indeed, in the large sample of Blaum et al (7), items predicting weight loss or low BMI were those included in the MNA and most of them in the MNA-SF. Furthermore, it was previously shown that the energy intake of malnourished subjects according to the MNA was below their needs, in contrast to subjects with MNA over 24 (31). This was confirmed elsewhere using other undernutrition criteria (12,32).…”
Section: Discussionmentioning
confidence: 57%
“…Associations between undernutrition and impaired function or high need of care, dementia, swallowing difficulties, constipation and agitation were also evidenced (12,31).…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, weight gain in undernourished geriatric rehabilitation patients during their hospital stay could improve their function in basic activities of daily life (Poulsen, 2005). Diminished functional ability, together with diminished cognitive function, has also been seen to be associated with nutritional risk in older patients (Pearson et al, 2001) and with undernutrition in frail older service flat residents (Ö dlund Olin et al, 2005).…”
Section: Discussionmentioning
confidence: 99%